Health disorders in workers associated with health risks at workplaces in mining industry in the Arctic (Analytical review) - А.G. Fadeev; D.V. Goryaev; N.V. Zaitseva; P.Z. Shur; S.V. Redko; V.А. Fokin (Analiz Riska Zdorovʹû, 2023)
The review analyzes a range and prevalence of health disorders in workers employed at mining enterprises in the Arctic and exposed to heterogeneous occupational factors. We revealed that working processes typical for basic occupations in under-ground mining involved exposure to a set of heterogeneous harmful and (or) hazardous occupational factors such as intense occupational noise; elevated vibration; aerosols with predominantly fibrogenic effects, dusts and chemicals; high hardness and intensity typical for physical work; non-ionizing electromagnetic radiation. It was shown that diseases of the ear and mastoid, vibration syndrome, diseases of the musculoskeletal system, respiratory diseases and diseases of the nervous system prevailed both in the structure of general morbidity and in occupational one typical for miners. To create proper working conditions and to minimize effects of harmful and hazardous occupational factors as well as occupational health risks, it is advisable to perform comprehensive hygienic assessment of introduced equipment, machinery and mechanisms; to establish levels and doses of occupational factors. Engineering and technical, technological, medical and preventive and treatment and health-improving activities should be developed on this basis with special emphasis on such occupational groups as drift miners, drill-operators, blasters, timbermen, operators of cargo handling machinery, drilling unit operators, miners in mining outputs and faces, repairmen, and electric gas welders. It seems extremely vital to apply risk assessment methodology to assess occupational health risks for workers employed in mining operations in the Norilsk industrial region considering climatic features of the Arctic. This assessment is important for substantiating relevant activities aimed at managing such risks and protecting workers’ health.